Should we consider microbiota-based interventions as a novel therapeutic strategy for schizophrenia? A systematic review and meta-analysis - Lucas Hassib; Alexandre Kanashiro; João Francisco Cordeiro Pedrazzi; Bárbara Ferreira Vercesi; Sayuri Higa; Íris Arruda; Yago Soares; Adriana de Jesus de Souza; Alceu Afonso Jordão; Francisco Silveira Guimarães; Frederico Rogério Ferreira (Brain, Behavior, & Immunity - Health)
Schizophrenia is a chronic psychiatric disorder characterized by a variety of symptoms broadly categorized into positive, negative, and cognitive domains. Its etiology is multifactorial, involving a complex interplay of genetic, neurobiological, and environmental factors, and its neurobiology is associated with abnormalities in different neurotransmitter systems. Due to this multifactorial etiology and neurobiology, leading to a wide heterogeneity of symptoms and clinical presentations, current antipsychotic treatments face challenges, underscoring the need for novel therapeutic approaches. Recent studies have revealed differences in the gut microbiome of individuals with schizophrenia compared to healthy controls, establishing an intricate link between this disorder and gastrointestinal health, and suggesting that microbiota-targeted interventions could help alleviate clinical symptoms. Therefore, this meta-analysis investigates whether gut microbiota manipulation can ameliorate psychotic outcomes in patients with schizophrenia receiving pharmacological treatment. Nine studies (n = 417 participants) were selected from 81 records, comprising seven randomized controlled trials and two open-label studies, all with a low risk of bias, included in this systematic review and meta-analysis. The overall combined effect size indicated significant symptom improvement following microbiota treatment (Hedges' g = 0.48, 95% CI = 0.09 to 0.88, p = 0.004, I2 = 62.35%). However, according to Hedges' g criteria, the effect size was small (approaching moderate), and study heterogeneity was moderate based on I2 criteria. This review also discusses clinical and preclinical studies to elucidate the neural, immune, and metabolic pathways by which microbiota manipulation, particularly with Lactobacillus and Bifidobacterium genera, may exert beneficial effects on schizophrenia symptoms via the gut-brain axis. Finally, we address the main confounding factors identified in our systematic review, highlight key limitations, and offer recommendations to guide future high-quality trials with larger participant cohorts to explore microbiome-based therapies as a primary or adjunctive treatment for schizophrenia.